APPLICATION OF PROBLEM-BASED LEARNING (PBL) LEARNING MODEL ON CLASS VIII STUDENT'S CRITICAL THINKING ABILITY STATE JUNIOR HIGH SCHOOL 6 BORONG - Yohana Melci Joni; Melkyanus Bili Umbu Kaleka; Yasinta Embu Ika (Program Studi Pendidikan IPA FKIP Universitas Jember, 2021)
This study aims to determine the effect of applying the problem-based learning (PBL) model on the critical thinking skills of eighth-grade students of SMP Negeri 6 Borong. The type of research used is quantitative with a quasi-experimental research design (quasi-experimental) with a Posttest- Only Control Group Design. The population in this study were all students of class VIII SMP Negeri 6 Borong totaling 89 people who were obtained using a random sampling technique. The data collection technique used a test in a description test to measure students' critical thinking skills. Data analysis used normality test, normality test, and hypothesis testing. The results of the study using SPSS 24 obtained the results of the research, namely a significant value for (sig 2- tailed) of 0.000 <0.05, which means that there is an effect of implementing the Problem Based Learning learning model on critical thinking skills so that H0 is rejected and H1 is accepted.